Perception of individuals in farming sector towards health care services in the implementation of the new national health financing scheme - A Azimatun Noor,; AM Mohd Rizal,; H Rozita,; SM Aljunid, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : Limited access to health services, variations in quality of health care and pressure to contain escalation of health care cost are problems in health care systems that are faced by all the societies in the world especially in developing countries. There is an urgent need to conduct a study to assess perception of individual towards health care services in the new planned National Healthcare Financing Scheme. Objective : The study objective is to examine the perception towards health care services among the farming community and to assess the willingness to contribute to The New National Health Financing Scheme. Methods : A cross sectional study involving farmers in the state of Selangor in Peninsular Malaysia was conducted. A total of 400 farmers as the household head were selected using multistage random sampling method. Results : The respondents’ mean score of perception towards public healthcare services were higher than the respondents’ mean score of perceptions towards private healthcare services except for accessibility and convenience aspects. There was no association between willingness to contribute to The New National Healthcare Financing Scheme and perception towards public healthcare services but there was association between willingness to contribute to The New National Healthcare Financing Scheme and perception towards private healthcare services. Conclusion : Perception towards healthcare services is an important element in the implementation of The New National Healthcare Financing Scheme as it will determine the willingness of an individual to contribute to it.